Forecasting Stock Crashes in Emerging Markets: A Comparative Machine Learning Study - Ahmed, Khaled Essam Hosny (2026)
A Master of Science thesis in Engineering Systems Management by Khaled Essam Hosny Ahmed entitled, “Forecasting Stock Crashes in Emerging Markets: A Comparative Machine Learning Study”, submitted in February 2026. Thesis advisor is Dr. Hussam AlShraideh and thesis co-advisor is Dr. Anis Samet. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).